On determination of effective mass of the delocalized positronium in NaCl crystals; Solid State Communications; Vol. 44, iss. 7 - Arefyev (Afef'ev, Arefiev) K. P. Konstantin Petrovich; Boev O. V.; Kuznetsov P. V.; Vorobiev S. A. (1982, 1982)
The angular correlation of the photons of two-quantum annihilation in NaCl crystal was measured at temperatures ranging from 77 to 500 K. The data obtained clearly showed a narrow peak which was earlier observed only at low temperatures. The positronium nature of this peak was examined by applying a magnetic field. The positronium effective mass was found to be (1.5±0.2)2 m0.